Direct writing of silver microfiber with precise control on patterning for robust and flexible ultrahigh-performance transparent conductor. (15th June 2020) - Chen, Tao; Li, Heping; Li, Jing; Hu, Sanyuan; Ye, Pin; Yan, Youwei
Graphical abstract: Abstract: Ultrafine silver fiber is an alternative to commercial indium tin oxide (ITO) as a new-generation flexible transparent conductor that can be used in flexible electronics. However, its primary limitation is the unrepeatable optoelectronic properties due to the disordered distribution of silver fibers. In this work, we report the in-situ direct writing of the silver microfiber pattern with high conductivity and transparency to attain a flexible transparent conductor. The silver network is composed of silver microfibers, which can be artificially designed and regularly patterned under the precise control of the fiber position and shape; this is crucial for regulating its optoelectronic properties. Herein, a high-performance conductor is achieved in the silver network with high stability. This novel conductor has a sheet resistance of 2 Ω sq −1 at 90% transparency, which corresponds to a high Figure of merit σ dc /σ opt  = 1742. The in-situ direct writing technique developed here is distinct from other fabrication methods because it requires no transfer steps, templates or heating. Further, this silver network is integrated into a light-printable rewritable device, and can be used as a wearable heater; this heater when driven by a 1.5 V battery attains a temperature of up to 55.6 ℃. Therefore, in-situ direct writing is expected to offer a new platform for facile, scalable, and ultralow-cost production of high-performance metal networks for flexible transparent conductors.